2012
DOI: 10.1021/bi2018305
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Heme Ligation Properties of Rv0203, a Secreted Heme Binding Protein Involved in Mycobacterium tuberculosis Heme Uptake

Abstract: The secreted Mycobacterium tuberculosis (Mtb) heme binding protein Rv0203 has been shown to play a role in Mtb heme uptake. In this work we use spectroscopic (absorption, electron paramagnetic resonance and magnetic circular dichrosim) methods to further characterize the heme coordination environments of His-tagged and native protein forms, Rv0203-His and Rv0203-notag, respectively. Rv0203-His binds the heme molecule through bis-His coordination and is low spin in both ferric and ferrous oxidation states. Rv02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 59 publications
5
58
1
Order By: Relevance
“…Biochemical studies indicate that heme dissociates from Rev-erb␤ too slowly to equilibrate with the heme pool and thus would be unable to act, as suggested previously (16,49), as an intracellular heme sensor. We also demonstrate that heme has only a minimal effect on the binding of NCoR1 to FLRev-erb␤, refuting our original hypothesis that full-length proteins could reproduce the effects of heme observed in the cell.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Biochemical studies indicate that heme dissociates from Rev-erb␤ too slowly to equilibrate with the heme pool and thus would be unable to act, as suggested previously (16,49), as an intracellular heme sensor. We also demonstrate that heme has only a minimal effect on the binding of NCoR1 to FLRev-erb␤, refuting our original hypothesis that full-length proteins could reproduce the effects of heme observed in the cell.…”
mentioning
confidence: 77%
“…In some cases, the affinity is so high that even the quadratic treatment does not provide correct K d values. For example, a recent report from our laboratory showed that the K d for Fe 3ϩ -heme binding to heme oxygenase-2 determined with stoichiometric equilibrium titrations was 70-fold higher (14 nM) than the value (0.2 nM) calculated from heme on-and off-rates (45 For the reasons just discussed, we measured the Fe 3ϩ -heme off-rates, the controlling factor in distinguishing heme affinity among a variety of heme proteins (49,75). We mixed FLReverb␤⅐Fe 3ϩ -heme complexes with 10-fold excess apomyoglobin and monitored the conversion of apo-to holomyoglobin at 408 nm ( Fig.…”
Section: Purification Of Flrev-erb␤ and Its Ability To Bind Co And Hementioning
confidence: 97%
“…The final purification step was performed by using an S200 10/30 Superdex column (GE Healthcare) equilibrated with a solution containing 50 mM Tris (pH 7.4) and 150 mM NaCl to yield 100% homogeneous Hal N . The percentage of heme was determined by using the pyridine hemochrome and Lowry assays (Bio-Rad) (64,65). To achieve fully heme-reconstituted Hal N , a hemin solution was added to a 1:1 molar ratio of heme to protein (Sigma) (64,65).…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of heme was determined by using the pyridine hemochrome and Lowry assays (Bio-Rad) (64,65). To achieve fully heme-reconstituted Hal N , a hemin solution was added to a 1:1 molar ratio of heme to protein (Sigma) (64,65). Crystals of heme-Hal N were grown at 90 mg/ml by a hanging-drop vapor diffusion method with a reservoir containing 0.2 M ammonium sulfate, 0.1 M BisTris (pH 5.5), and 21% polyethylene glycol 3350 (PEG 3350) with a 1:1 (vol/vol) protein-to-reservoir drop.…”
Section: Methodsmentioning
confidence: 99%
“…Solutions were made, and titration experiments were performed as described previously (21,22). Heme (23) and PPIX (24) solutions were freshly prepared prior to each experiment.…”
Section: Heme and Protoporphyrin IX (Ppix) Titration Into Mt-dypmentioning
confidence: 99%